2003
DOI: 10.1111/j.1751-0813.2003.tb12509.x
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasmosis in Indo‐Pacific humpbacked dolphins (Sousa chinensis), from Queensland

Abstract: Objective To describe the clinical signs, gross pathology, serology, bacteriology, histopathology, electron microscopy and immunohistochemistry findings associated with toxoplasmosis in four Indo‐Pacific humpbacked dolphins (Sousa chinensis) that stranded in Queensland in 2000 and 2001. Design Clinical assessment, gross necropsy, and laboratory examinations. Procedure Necropsies were performed on four S chinensis to determine cause of death. Laboratory tests including serology, bacteriology, histopathology and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 12 publications
(13 reference statements)
0
28
0
Order By: Relevance
“…[16]) and Indo-Pacific bottlenose dolphins [17]. At present, it is not considered a significant cause of cetacean mortality in Australia.…”
Section: Introductionmentioning
confidence: 99%
“…[16]) and Indo-Pacific bottlenose dolphins [17]. At present, it is not considered a significant cause of cetacean mortality in Australia.…”
Section: Introductionmentioning
confidence: 99%
“…Catfish possess serrated spines composed of dense bone tissue with the ability to harm and kill dolphins (Barros and Cockcroft 1999). Stingray barbs are also known to pose as a threat to dolphins (Duignan et al 2000, Spanier et al 2000, and have been found embedded in the bodies of dead Australian humpback dolphins (Bowater et al 2003). Thus, it is feasible that the humpback dolphin may have used the sponge as a ''protective glove'' while searching for food in the sea bottom.…”
mentioning
confidence: 99%
“…Ingestion in contaminated food is one of the infection routes of these pathogens. Recently, T. gondii infection has been reported in wild marine mammals, including several species of cetaceans [1,2,4,16,18,19]. As for Brucella species, infection has been observed in a wide range of species of marine mammals [6,17,22].…”
mentioning
confidence: 99%